Fecal microbiota transplantation repairs intestinal permeability and regulates the expression of 5-HT to influence alcohol-induced depression-like behaviors in C57BL/6J mice - Li, Dezhi; Liang, Wei; Zhang, Wentong; Huang, Zhiqiang; Liang, Haipeng; Liu, Qing (Frontiers in Microbiology, 2024)
The epidemic of alcohol abuse affects millions of people worldwide.Relevant evidence supports the notion that the gut microbiota (GM) plays a crucial role in central nervous system (CNS) function, and its composition undergoes changes following alcohol consumption. Therefore, the purpose of this study was to investigate the effect of reconstructing the gut microbiota by fecal microbiota transplantation (FMT) on alcohol dependence. Here, we established an alcohol dependence model with C57BL/6J mice and proved that FMT treatment improved anxiety-like behavior and alcohol-seeking behavior in alcohol-dependent mice. Additionally, we found that the expression of the intestinal intercellular tight junction structure proteins ZO-1 and occludin was significantly increased after FMT. FMT repaired intestinal permeability in alcohol-dependent mice and decreased the levels of lipopolysaccharide (LPS) and proinflammatory factors. Moreover, the serotonin (5-hydroxytryptamine, 5-HT) content was significantly increased in alcohol-dependent mouse intestinal and brain tissues after receiving the fecal microbiome from healthy mice. 16S rRNA sequencing demonstrated that FMT markedly reshaped the composition of the gut microbiota and elicited changes in the intestinal barrier and 5-HT levels. Collectively, our results revealed that FMT has a palliative effect on alcohol dependence and explored the underlying mechanisms, which provides new strategies for the treatment of alcohol dependence.